IDENTIFICATION AND CODING OF ELLIOT WAVE PATTERN - Vaghela, Vaidehi; Gor, Ravi (International Journal of Engineering Science Technologies, 2022)
Prediction of stock price and modelling of market pattern are quite difficult and complex to understand itself. There are hidden factors of market like effect of news, sentiment of crowd etc. which play an important role of modelling the market pattern. The modelling of market patterns was primarily developed by R.N. Elliott. The Elliott Wave theory was described subjectively in literature and wave patterns cannot be identify easily. In this work, we mainly focus on identification of wave pattern through Fractal indicators and Awesome Oscillator using R programming.